Halogen-free flame-retardant semi-aromatic polyamide composite material as well as preparation method and application thereof
By using halogen-free flame-retardant semi-aromatic polyamide composite in LED reflective bracket materials, combined with the synergistic reaction of titanium dioxide, wollastonite and hydrotalcite, the existing materials have been solved, and the effects of high flame retardant grade and high light reflectivity are achieved.
Patent Information
- Application Number
- CN202411645824.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing LED reflective bracket materials are not fire-resistant, the flame retardant level does not reach the UL94 V-0 level, and the initial reflectivity after adding flame retardant is low, and the yellowing resistance is poor, which affects the brightness and aging performance of the LED light source.
Halogen-free flame-retardant semi-aromatic polyamide composite material is used to improve the light reflectivity and yellowing resistance through the synergistic reaction between titanium dioxide, wollastonite and hydrotalcite of a specific weight ratio and the halogen-free flame retardant performance. Through the specific structure of PA5T/X resin and the selection of flame retardant, the high flame retardant grade and good light reflection performance of the composite material are ensured.
It has achieved a high flame retardant grade (V-0 level) of halogen-free flame retardant semi-aromatic polyamide composite material, with a light reflectivity of 460nm >90%, and has good yellowing resistance, which is suitable for LED light source reflective bracket materials.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a halogen-free flame-retardant semi-aromatic polyamide composite material and a preparation method and application thereof. Background Art
[0002] LED light sources are mainly composed of semiconductor chips, LED light source reflective brackets, gold wires, and packaging glue. The LED light source reflective bracket is the "skeleton" of the LED light source and is also a functional part. The LED packaging process requires solid crystals, wire bonding, and packaging glue curing, and other materials and components are integrated here. The LED reflective bracket needs to reflect the light emitted by the LED chip at a certain angle to reduce light loss, and then pass it through packaging materials such as epoxy resin or silicone to form a light source for LED lighting or display. The LED reflective bracket material is a core material for LED lighting and is directly related to the performance and life of the LED light source. Generally, the existing LED lamp beads emit a light source with a wavelength of 460nm. Therefore, the higher the light reflectivity of the material in the 460nm band, the more conducive it is to be used in the LED lamp reflective bracket.
[0003] At present, in the application of LED lighting and LED display screens, with the increasing power of lighting lamp beads and the development trend of increasing screen area of LED display screens, higher requirements are put forward for the safety and reliability of light sources. In particular, outdoor lighting sources and display lamp beads age quickly due to high temperature, rain, cold and heat shock. In relatively humid climate seasons, rain and dew can easily penetrate into LED lamps, causing short circuits of electronic components inside the LED display screen and causing fires. Therefore, the fire resistance level requirements for LED light source bracket materials are getting higher and higher. However, the current LED reflective bracket materials on the market are still not fireproof, and the flame retardant level does not reach the UL94 V-0 level.
[0004] Since the initial reflectivity of the LED bracket material is low and the yellowing resistance is poor after adding flame retardants, the brightness and aging performance of the LED light source are seriously affected. Summary of the invention
[0005] The purpose of the present invention is to overcome the above technical defects and provide a halogen-free flame retardant semi-aromatic polyamide composite material with high flame retardancy, high 460nm light transmittance and good yellowing resistance, as well as a preparation method and application thereof.
[0006] The present invention is achieved through the following technical solutions: A halogen-free flame-retardant semi-aromatic polyamide composite material, comprising the following components in parts by weight: PA5T / X resin 40-75 parts; 5-25 parts of halogen-free flame retardant; 25-60 parts of reflective filler; The reflective pigment is selected from titanium dioxide: wollastonite: hydrotalcite weight ratio = (8-21): (5-12): 1; Wherein, the PA5T / X resin, based on the molar percentage of PA5T / X, has a 5T unit content of 40-70 mol%, an X unit content of 30-60 mol%, and the X unit is not 5T; wherein the X unit is composed of a diacid unit and a diamine unit, the diacid unit is selected from at least one of a terephthalic acid unit, an isophthalic acid unit, a 1,6-adipic acid unit, and a 1,10-decanedioic acid unit, and the diamine unit is selected from at least one of a 1,5-pentanediamine unit, a 1,6-hexanediamine unit, a 1,9-nonanediamine unit, a 2-methyl-1,5-pentanediamine unit, a 2-methyl-1,8-octanediamine unit, a 1,10-decanediamine unit, and a 1,12-dodecanediamine unit; The halogen-free flame-retardant semi-aromatic polyamide composite material is subjected to differential scanning calorimetry, and the half-height width ΔT1 / 2 of the crystallization peak measured at 4-15°C after heating to 350°C once and cooling at a rate of 20°C / min.
[0007] Preferably, the weight ratio of titanium dioxide:wollastonite:hydrotalcite is (10-15):(7-10):1.
[0008] The halogen-free flame retardant is selected from at least one of diethyl aluminum phosphinate, diethyl zinc phosphinate, methyl ethyl aluminum phosphinate, ethyl butyl aluminum phosphinate, and ethyl hexyl aluminum phosphinate; preferably, the halogen-free flame retardant is selected from diethyl aluminum phosphinate.
[0009] Preferably, the PA5T / X resin has a 5T unit content of 50-60 mol%, and an X unit content of 40-50 mol%.
[0010] The PA5T / X resin is selected from at least one of PA5T / 6T, PA5T / 9T, PA5T / 10T, PA5T / 12T, PA5T / 56, PA5T / 510, and PA5T / 5I.
[0011] The PA5T / X resin of the present invention may be a commercially available product, or may be synthesized according to the following method: (1) Prepolymerization: Put the polymerization monomer, end-capping agent benzoic acid and deionized water into a stainless steel autoclave equipped with mechanical stirring. Evacuate and use N 2 After three replacements, the temperature was raised and stirred, and the temperature was raised to 180°C at a rate of 5°C / min. After the temperature was kept constant for 60 minutes, the temperature was raised to 270°C at a rate of 2°C / min, and then slowly stirred and kept constant for 4 hours to allow the prepolymerization reaction to proceed fully. After the constant temperature was completed, the temperature was slowly raised to 280°C, and drainage began to be carried out to normal pressure. When the pressure dropped to normal pressure, the drainage valve was closed, the reaction was completed, and the material was discharged after the temperature dropped to room temperature.
[0012] (2) Solid phase viscosity enhancement: The material prepared in the prepolymerization process is placed in a vacuum drum, the drum speed is set at 10 r / min, and the vacuum degree is set at 30 Pa. The temperature is increased at a rate of 20°C / min. When the temperature reaches 265°C, a sample is taken to test the viscosity, and the discharge end point is determined based on the viscosity result.
[0013] The number average molecular weight of the PA5T / X resin capable of achieving the purpose of the present invention is in the range of 1000-30000.
[0014] After experiments, the average particle size range of titanium dioxide and hydrotalcite that can achieve the purpose of the present invention is 0.09-0.62 microns. Preferably, the average particle size range of titanium dioxide and hydrotalcite is 0.15-0.35 microns, and more preferably 0.20-0.30 microns; the average diameter of wollastonite is 4-20μm, and the average length is 10-250μm; preferably, the average diameter is 6-13μm, and the average length is 60-120μm.
[0015] By weight, the invention further comprises 0-2 parts of auxiliary agents, wherein the auxiliary agents are selected from at least one of antioxidants and lubricants.
[0016] The 460nm light reflectivity of the halogen-free flame-retardant semi-aromatic polyamide composite material of the invention is greater than 90%.
[0017] The preparation method of the halogen-free flame-retardant semi-aromatic polyamide composite material of the present invention comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder, with the screw temperature ranging from 280 to 330° C. and the rotation speed being 400 to 500 r / min, to obtain the halogen-free flame-retardant semi-aromatic polyamide composite material.
[0018] The halogen-free flame-retardant semi-aromatic polyamide composite material of the present invention is used for preparing an LED light source reflective bracket and an outdoor LED display screen light source reflective bracket.
[0019] Compared with the prior art, the present invention has the following beneficial effects: In the prior art, halogen-free flame retardants easily cause polyamide composite materials to turn yellow. The present invention mainly uses titanium dioxide, wollastonite and hydrotalcite in a specific weight ratio. Wollastonite and hydrotalcite can react synergistically with the selected flame retardant to reduce the amount of flame retardant added, thereby improving light reflectivity; the specific content of hydrotalcite can absorb the acidic substances in the flame retardant to improve the yellowing resistance; at the same time, the composite filler cooperates with the PA5T / X resin with a specific repeating unit structure, which can not only make the crystallization peak half-height width ΔT1 / 2 of the halogen-free flame-retardant semi-aromatic polyamide composite material 4-15°C, avoiding the influence of the flame retardant on the molding cycle, but also the yellowing resistance of the resin under the system of the present invention is better, and the initial light reflectivity and yellowing resistance are improved. Not only can the 460nm light reflectivity of the composite material be greater than 90%, but it also has the effect of yellowing resistance and V-0 flame retardancy, so that the halogen-free flame-retardant semi-aromatic polyamide composite material of the present invention is suitable for use as a reflective bracket material for LED light sources. DETAILED DESCRIPTION
[0020] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0021] The sources of raw materials used in the present invention are as follows: PA5T / 6T-A: 5T unit content 40 mol%, 6T unit content 60 mol%, number average molecular weight 8834, homemade; PA5T / 6T-B: 5T unit content 50 mol%, 6T unit content 50 mol%, number average molecular weight 9138, homemade; PA5T / 6T-C: 5T unit content 60mol%, 6T unit content 40mol%, number average molecular weight 8410, homemade; PA5T / 6T-D: 5T unit content 70 mol%, 6T unit content 30 mol%, number average molecular weight 8675, homemade; PA5T / 6T-E: 5T unit content 30 mol%, 6T unit content 70 mol%, number average molecular weight 9355, homemade; PA5T / 6T-F: 5T unit content 80 mol%, 6T unit content 20 mol%, number average molecular weight 8328, homemade; PA5T / 9T: 5T unit content 40 mol%, 9T unit content 60 mol%, number average molecular weight 12600, homemade; PA5T / 10T: 5T unit content 40 mol%, 10T unit content 60 mol%, number average molecular weight 5377, homemade; PA5T / 12T: 5T unit content 40 mol%, 12T unit content 60 mol%, number average molecular weight 18772, homemade; PA5T / 56: 5T unit content 40 mol%, 56 unit content 60 mol%, number average molecular weight 23180, homemade; PA5T / 510-A: 5T unit content 40 mol%, 510 unit content 60 mol%, number average molecular weight 11350, homemade; PA5T / 510-B: 5T unit content 50 mol%, 510 unit content 50 mol%, number average molecular weight 12722, homemade; PA5T / 510-C: 5T unit content 60 mol%, 510 unit content 40 mol%, number average molecular weight 12005, homemade; PA5T / 510-D: 5T unit content 70 mol%, 510 unit content 30 mol%, number average molecular weight 11907, homemade; PA5T / 510-E: 5T unit content 30 mol%, 510 unit content 70 mol%, number average molecular weight 12503, homemade; PA5T / 510-F: 5T unit content 80 mol%, 510 unit content 20 mol%, number average molecular weight 11554, homemade; Number average molecular weight: The weight average molecular weight (Mw) and number average molecular weight (Mn) of PA5T / X resin samples were determined by gel permeation chromatography (GPC). Agilent HPLC-1260 high performance liquid chromatograph, equipped with: Eppendorf column oven, Shodex KF-801, 802, 802.5 and 803 gel permeation chromatography columns, differential detector, G7129A autosampler. Hexafluoroisopropanol was used as the mobile phase, and the molecular weight of the resin was determined at a column temperature of 40 °C. The data were processed using the chromatography workstation cirrus software to obtain the number average molecular weight distribution Mn.
[0022] The wollastonite used in the present invention is purchased from the market and then screened to obtain the required average diameter and average length range: Wollastonite A: average diameter, 17 μm, average length, 180 μm; Wollastonite B: average diameter, 8 μm, average length, 110 μm; Wollastonite C: average diameter, 4 μm, average length, 60 μm; Wollastonite D: average diameter is 20 μm, average length is 210 μm.
[0023] Titanium dioxide was purchased from Longbai Group, and hydrotalcite was purchased from Kanggaote New Material Technology Co., Ltd. The raw materials with the required average particle size were obtained by screening: Titanium dioxide A: average particle size 0.16 microns; Titanium dioxide B: average particle size 0.21 microns; Titanium dioxide C: average particle size 0.30 microns; Titanium dioxide D: average particle size 0.35 microns; Titanium dioxide E: average particle size 0.11 microns; Titanium dioxide F: average particle size 0.51 microns; Hydrotalcite A: average particle size 0.15 μm; Hydrotalcite B: average particle size 0.20 μm; Hydrotalcite C: average particle size 0.28 μm; Hydrotalcite D: average particle size 0.34 μm; Hydrotalcite E: average particle size 0.09 μm; Hydrotalcite F: average particle size 0.62 μm; Aluminum diethylphosphinate: purchased from Clariant, Exolit OP1230.
[0024] Antioxidant: Irganox1098, hindered phenol antioxidant.
[0025] Embodiment and comparative example Preparation method of semi-aromatic polyamide molding composite material: according to the ratio, the components are mixed evenly, and extruded into granules by a twin-screw extruder, the screw temperature range is 280-330°C, and the rotation speed is 400-500r / min to obtain a halogen-free flame-retardant semi-aromatic polyamide composite material.
[0026] Various test methods: (1) Reflectivity: A test piece having a length of 60 mm, a width of 60 mm and a thickness of 1 mm was prepared by injection molding the polyamide molding composition. The reflectivity of the test piece to light having a wavelength of 460 nm was measured using a Color Eye 7000A colorimeter.
[0027] (2) Yellowing resistance: Use Color Eye 7000A colorimeter to measure the initial L1, a1, b1 values of the test piece, as well as the L2, a2, b2 values after thermal aging at 180°C for 8 h. Calculate the material ΔE using the following formula, where ΔL=L2-L1, Δa=a2-a1, Δb=b2-b1; .
[0028] (3) Crystallization peak half-width ΔT1 / 2 of halogen-free flame-retardant semi-aromatic polyamide composite materials: Using a differential scanning calorimeter manufactured by NETZSCH, the temperature was raised from 30°C to 350°C at a rate of 20°C / min in a nitrogen atmosphere. After keeping the temperature constant for 2 minutes, the temperature was cooled at a rate of 20°C / min. The crystallization peak temperature that appeared at this time was set as the crystallization temperature Tc (°C), and the temperature at half the peak width was set as the crystallization peak half-width ΔT 1 / 2 (4) Flame retardancy: Vertical burning, measured at 1.6 mm according to UL94 standard.
[0029] Table 1: Combination contents and test results of halogen-free flame-retardant semi-aromatic polyamide composite materials of Examples 1-6 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 PA5T / 6T-A 53 40 75 53 53 53 Diethylaluminum hypophosphite 10 5 25 10 10 10 Titanium Dioxide A 20 32 15 22 21 22.7 Wollastonite A 15 24 10 12.5 14.5 13.2 Hydrotalcite A 2 3 1.5 2.5 1.5 1.1 Antioxidants 0.5 0.5 0.5 0.5 0.5 0.5 Flame retardant V-0 V-0 V-0 V-0 V-0 V-0 Crystallization peak half-height width℃ 5.6 5.9 5.3 5.5 5.4 5.8 Reflectivity R460,% 93.4 94.5 91.0 91.8 92.9 90.8 Yellowing resistance ΔE 3.3 2.2 9.4 5.1 3.1 5.6 It can be seen from Examples 1-3 that the content of the flame retardant significantly affects the light reflectivity and yellowing resistance of the composite material, while the technical solution of the present invention can limit ΔE to below 10, and the R460 reflectivity is greater than 90%.
[0030] It can be seen from Examples 1 / 4 / 5 / 6 that the preferred weight ratio of titanium dioxide: wollastonite: hydrotalcite not only has a higher reflectivity but also better yellowing resistance.
[0031] Table 2: Combination contents and test results of halogen-free flame-retardant semi-aromatic polyamide composite materials of Examples 7-13 Example 7 Example 8 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 PA5T / 6T-B 53 PA5T / 6T-C 53 PA5T / 6T-D 53 PA5T / 9T 53 PA5T / 10T 53 PA5T / 12T 53 PA5T / 56 53 Diethylaluminum hypophosphite 10 10 10 10 10 10 10 Titanium Dioxide A 20 20 20 20 20 20 20 Wollastonite A 15 15 15 15 15 15 15 Hydrotalcite A 2 2 2 2 2 2 2 Antioxidants 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Flame retardant V-0 V-0 V-0 V-0 V-0 V-0 V-0 Crystallization peak half-width℃ 6.2 8.8 10.3 6.9 8.5 13.2 14.5 Reflectivity R460,% 94.6 94.0 91.9 91.3 91.4 91.3 91.7 Yellowing resistance ΔE 2.5 2.8 6.0 5.2 4.6 4.9 5.3 Table 3: Combination contents and test results of halogen-free flame-retardant semi-aromatic polyamide composite materials of Examples 14-17 Embodiment 14 Embodiment 15 Example 16 Embodiment 17 PA5T / 510-A 53 PA5T / 510-B 53 PA5T / 510-C 53 PA5T / 510-D 53 Diethylaluminum hypophosphite 10 10 10 10 Titanium Dioxide A 20 20 20 20 Wollastonite A 15 15 15 15 Hydrotalcite A 2 2 2 2 Antioxidants 0.5 0.5 0.5 0.5 Flame retardant V-0 V-0 V-0 V-0 Crystallization peak half-width℃ 12 13.2 14.3 14.9 Reflectivity R460,% 92.0 93.7 94.4 92.4 Yellowing resistance ΔE 7.3 5.9 4.2 6.9 It can be seen from Examples 1 / 7-17 that the preferred PA5T / X resin has a 5T unit content of 50-60 mol%, and an X unit content of 40-50 mol%.
[0032] Table 4: Combination contents and test results of halogen-free flame-retardant semi-aromatic polyamide composite materials of Examples 18-22 Embodiment 18 Embodiment 19 Embodiment 20 Embodiment 21 Embodiment 22 PA5T / 6T-A 53 53 53 53 53 Diethylaluminum hypophosphite 10 10 10 10 10 Titanium dioxide selection B C D E F Titanium dioxide content 20 20 20 20 20 Wollastonite selection B C D B B Wollastonite content 15 15 15 15 15 Hydrotalcite Selection B C D E F Hydrotalcite content 2 2 2 2 2 Antioxidants 0.5 0.5 0.5 0.5 0.5 Flame retardant V-0 V-0 V-0 V-0 V-0 Crystallization peak half-height width℃ 5.2 5.9 6.3 5.1 6.5 Reflectivity R460,% 94.7 94.5 92.4 91.9 91.8 Yellowing resistance ΔE 2.7 3.0 3.9 4.7 5.5 It can be seen from Examples 1 / 18-22 that the reflectivity is higher and the yellowing resistance is better when the parameters of titanium dioxide, wollastonite and hydrotalcite are preferred.
[0033] Table 5: Combination contents and test results of halogen-free flame-retardant semi-aromatic polyamide composite materials of comparative examples 1-7 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 PA5T / 6T-A 53 53 53 PA5T / 6T-E 53 PA5T / 6T-F 53 PA5T / 510-E 53 PA5T / 510-F 53 Diethylaluminum hypophosphite 10 10 10 10 10 10 10 Titanium Dioxide A 20 20 20 20 22 30 10 Wollastonite A 15 15 15 15 15 6 25 Hydrotalcite A 2 2 2 2 0 1 2 Antioxidants 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Flame retardant V-0 V-0 V-0 V-0 V-0 V-0 V-0 Crystallization peak half-height width℃ 3.9 16 10.2 17 6.0 5.8 5.6 Reflectivity R460,% 92.0 89.2 91.5 91.3 90.1 89 85 Yellowing resistance ΔE 10.8 12.3 15.1 17.4 19 10 15 It can be seen from Comparative Examples 1-2 that if the unit content of PA5T / 6T is not within the range of the present invention, the half-width of the crystallization peak is too low or too high, and even if a light reflectance of more than 90% can be obtained, the yellowing resistance is poor.
[0034] It can be seen from Comparative Example 3 that the repeating unit of PA5T / 510 is not within the scope of the present invention. Even if the half-width of the crystallization peak is within the scope of the present invention, its yellowing resistance is insufficient.
[0035] It can be seen from Comparative Example 4 that when the 5T unit content in PA5T / 510 is too high (80 mol%), the half-width of the crystallization peak is too high and the yellowing resistance is poor.
[0036] It can be seen from Comparative Example 5 that if hydrotalcite is not contained, the yellowing resistance is poor.
[0037] It can be seen from Comparative Examples 6-7 that if the ratio of titanium dioxide, wollastonite and hydrotalcite is not within the range of the present invention, the reflectivity and yellowing resistance are poor.
Claims
1. A halogen-free flame-retardant semi-aromatic polyamide composite material, characterized in that: By weight, it includes the following components: PA5T / X resin 40-75 parts; 5-25 parts of halogen-free flame retardant; 25-60 parts of reflective filler; The reflective pigment is selected from titanium dioxide: wollastonite: hydrotalcite weight ratio = (8-21): (5-12): 1; Wherein, the PA5T / X resin, based on the molar percentage of PA5T / X, has a 5T unit content of 40-70 mol%, an X unit content of 30-60 mol%, and the X unit is not 5T; wherein the X unit is composed of a diacid unit and a diamine unit, the diacid unit is selected from at least one of a terephthalic acid unit, an isophthalic acid unit, a 1,6-adipic acid unit, and a 1,10-decanedioic acid unit, and the diamine unit is selected from at least one of a 1,5-pentanediamine unit, a 1,6-hexanediamine unit, a 1,9-nonanediamine unit, a 2-methyl-1,5-pentanediamine unit, a 2-methyl-1,8-octanediamine unit, a 1,10-decanediamine unit, and a 1,12-dodecanediamine unit; The halogen-free flame-retardant semi-aromatic polyamide composite material is subjected to differential scanning calorimetry, and the half-height width ΔT1 / 2 of the crystallization peak measured at 4-15°C after heating to 350°C once and then cooling at a rate of 20°C / min.
2. The halogen-free flame-retardant semi-aromatic polyamide composite material according to claim 1, characterized in that: Weight ratio of titanium dioxide: wollastonite: hydrotalcite = (10-15): (7-10):
1.
3. The halogen-free flame-retardant semi-aromatic polyamide composite material according to claim 1, characterized in that: The halogen-free flame retardant is selected from at least one of diethyl aluminum phosphinate, diethyl zinc phosphinate, methyl ethyl aluminum phosphinate, ethyl butyl aluminum phosphinate, and ethyl hexyl aluminum phosphinate; preferably, the halogen-free flame retardant is selected from diethyl aluminum phosphinate.
4. The halogen-free flame-retardant semi-aromatic polyamide composite material according to claim 1, characterized in that: The PA5T / X resin has a 5T unit content of 50-60 mol%, and an X unit content of 40-50 mol%.
5. The halogen-free flame-retardant semi-aromatic polyamide composite material according to claim 1, characterized in that: The PA5T / X resin is selected from at least one of PA5T / 6T, PA5T / 9T, PA5T / 10T, PA5T / 12T, PA5T / 56, PA5T / 510, and PA5T / 5I.
6. The halogen-free flame-retardant semi-aromatic polyamide composite material according to claim 1, characterized in that: The average particle size range of the titanium dioxide and hydrotalcite is 0.09-0.62 microns, preferably 0.15-0.35 microns, more preferably 0.20-0.30 microns; the average diameter of the wollastonite is 4-20 μm, and the average length is 10-250 μm; preferably the average diameter is 6-13 μm, and the average length is 60-120 μm.
7. The halogen-free flame-retardant semi-aromatic polyamide composite material according to claim 1, characterized in that: By weight, the invention further comprises 0-2 parts of auxiliary agents, wherein the auxiliary agents are selected from at least one of antioxidants and lubricants.
8. The halogen-free flame-retardant semi-aromatic polyamide composite material according to any one of claims 1 to 7, characterized in that: The 460nm light reflectivity of the halogen-free flame-retardant semi-aromatic polyamide composite material is greater than 90%.
9. The method for preparing the halogen-free flame-retardant semi-aromatic polyamide composite material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder to obtain a halogen-free flame-retardant semi-aromatic polyamide composite material.
10. Use of the halogen-free flame-retardant semi-aromatic polyamide composite material according to any one of claims 1 to 8, characterized in that: Used for preparing LED light source reflective brackets and outdoor LED display light source reflective brackets.
Citation Information
Patent Citations
Yellowing-resistant and flame-retardant polyamide composition and preparation method thereof
CN110229514A
Furan diacid-based polyamide, preparation method thereof and furan diacid-based polyamide composition
CN113896886A
Polyamide composite material with high weld mark strength as well as preparation method and application thereof
CN114656785A